Chronic early-life lead exposure sensitizes adolescent rats to cocaine: Role of the dopaminergic system - Albores-Garcia, Damaris; Stansfield, Kirstie H.; McGlothan, Jennifer L.; Bursac, Zoran; Guilarte, Tomás R. (Frontiers in Molecular Neuroscience, 2022)
Exposure to heavy metals has been associated with psychiatric disorders and recent studies suggest an association between childhood lead (Pb2+) intoxication and schizophrenia (SZ). In animal models, Pb2+ exposure recapitulates key neuropathological and dopaminergic system alterations present in SZ. Given the high comorbidity of mental disorders such as SZ and substance abuse, and recent evidence showing that Pb2+ exposure affects addiction circuits, we hypothesized that early life Pb2+ exposure could sensitize neuronal systems relevant to SZ and substance abuse. To this goal, we examine the effect of chronic developmental Pb2+ exposure on the acute locomotor response to cocaine (0, 5, and 15 mg.kg-1) and behavioral sensitization. We examined the role of the dopaminergic system in the psychostimulant effects of cocaine, and measured D1-dopamine receptor (D1R) levels in the rat brain using [3H]-SCH23390 quantitative receptor autoradiography as well as the ability of the D1R antagonist SCH23390 to block the cocaine effects on locomotor activation. These studies were performed in male and female rats at different developmental ages consisting of juveniles (postnatal, PN14), early-adolescent (PN28), late adolescent (PN50), and adults (PN120). Our results show that chronic developmental Pb2+ exposure increases the acute locomotor response to cocaine in Pb2+-exposed male adolescent (PN28 and PN50) rats at the high dose of cocaine, and in adolescent female rats, but only at the low dose of cocaine. No changes in the locomotor activation were detected in adult rats. Behavioral sensitization experiments showed a sustained sensitization in early adolescent Pb2+-exposed male but not female rats. The cocaine-induced effects on locomotor activity were abrogated by injection of a D1R antagonist suggesting the involvement of this dopamine receptor subtype. Furthermore, Pb2+-induced increases D1R levels in several brain regions were prominent in juveniles and early adolescence but not in late adolescence or in adults. In summary, early chronic developmental Pb2+ exposure results in age and sex-dependent effect on the locomotor response to cocaine, suggesting differential susceptibilities to the neurotoxic effects of Pb2+ exposure. Our data provides further support to the notion that Pb2+ exposure is an environmental risk factor for psychiatric disorders and substance abuse.